OBSTETRICS OUTCOME AT TERM IN MECONIUM STAINED AMNIOTIC FLUID – A RETROSPECTIVE STUDY. - DR A.K.MAHAPATRO,; DR SEETESH GHOSE., (International Journal of Pharma and Bio Sciences, 2014)
The purpose of this study was to find out prevalence ,risk factors, mode of delivery, & perinatal out come in Meconium stained amniotic fluid (MSAF) during delivery At term pregnancy.Study design-this retrospective study was conducted in MGMC&RI,puducherry with womens at 37-42 wks of gestation those were meconium stained amniotic fluid during labour & delivery.Different maternal outcome like mode of delivery,indication for operative delivery & perinatal outcome in relation to low apgar score,neonatal intensive care unit( Nicu) admission,meconium aspiration syndrome(MAS),perinatal asphyxia & neonatal death were analysed .Result— Prevalence of meconium stained amniotic fluid during labour & delivery was 12.42% during study period.Most of the cases were primigravida (85%) with mean age & gestational age of-24.99 yrs & 39.44 wks respectively. Postdated pregnancy (32.85%) & oligo hydramnios(18.57%) were the two major risk factor for meconium stained amniotic fluid.Caesarean section (C.S) was the most common mode of delivery (84.28%) due to fetal distress & thick meconium stained liquor(40.71%).20% of cases were admitted to Nicu for low apgar score at birth.50% of nicu admission were due to MAS & its complication.There were two(7.14% of nicu admission) neonatal death due to MAS & its complication inspite of early active intervention in our study. Meconium stained amniotic fluid during labour & delivery is definite direct & indirect evidence of fetal distress(FD) .Grading of meconium stained amniotic fluid was a severe adverse effect in perinatal outcome. Instead of early active intervention there were early neonatal death in our study. So the outcome of meconium stained amniotic fluid during labour & delivery is unpredictable.